Pierwsze wyznanie Synostwa Bożego przez Jezusa (Łk 2, 41–52) - Stanisław Witkowski (Polonia Sacra)
Luke 2: 41–52, presents Jesus who is not only man, but also the Son of God, the one who has a special, unique relationship with his Father in heaven. Jesus is aware of this even as a παῖς, that is in his childhood. He knows that his priority mission which originates in God’s mandate, is his presence in the house of his Father that means fulfilling the task of teaching in the temple. This became clear during his pilgrimage to Jerusalem. Without asking his parents’ permission, of his own will, he stays in the Holy City and anticipates his future mission. His obedience to the heavenly Father takes priority over his filial subordination to Joseph and Mary, who did not understand this mystery. It turns out that faith in the mystery of Jesus is not given to man once and for all. It develops through reflection on the identity of Jesus and ultimately leads to the primacy of the will of God over human will.